“Patronage, like Hamlet’s ghost will not down!”: Ontario’s Farmer-Labour Government and Political Patronage, 1919-1923 - Sholdice, Mark (Ontario History)

(untitled) (The Ontario Historical Society, 2014)
This article examines the issue of political patronage during the tenure of the United Farmers of Ontario (UFO)-Independent Labor Party (ILP) coalition government in Ontario, which held office between 1919 and 1923. The reform of political patronage became the focus of profound controversy during the UFO-ILP government because of an unresolved contradiction between the inequality inherent in the practice, and the importance of patronage to the agrarian community. Politically motivated appointments were not just result of simple hypocrisy but came about because of the government’s desire to include greater numbers of farmers and workers in the province’s political system.